Surface nanopatterning of metal thin films by physical vapour deposition onto surface-modified silicon nanodots - Azzaroni, Omar (2004)
Nanostructuring of metallic and semiconductor surfaces in the sub-100 nm range is a key point in the development of future technologies. In this work we describe a simple and low-cost method for metal nanostructuring with 50 nm lateral and 6 nm vertical resolutions based on metal film deposition on a silane-derivatized nanostructured silicon master. The silane monolayer anti-sticking properties allow nanopattern transfer from the master to the deposited metal films as well as easy film detachment. The method is non-destructive, allowing the use of the derivatized master several times without damaging. Potential applications of the method are in the field of high-density data storage, heterogeneous catalysis and electrocatalysis, microanalysis (sensors and biosensors) and new optical devices.